Integrasi Bahasa Indonesia dan Bahasa Daerah Maumere dalam Pembelajaran Akademik : Strategi Penguatan Literasi, Identitas Lokal, dan Kompetensi Berbahasa Mahasiswa - Noorsetiawan Yusup; Yovina Merlianti; Cristiano A.C. Goan; Yeremias Bardi; Maria Janang Cindy Stevani Masneno; Maria Erista Punya Yenista Dua Sonang (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study explores the integration of Indonesian and the Maumere local language in academic learning, particularly in the Indonesian Language course at Universitas Muhammadiyah Maumere. The research is grounded in concerns over the weakening of local linguistic identity within higher education and the dominance of monolingual academic practices that often marginalize students’ cultural backgrounds. The objective of this study is to analyze how the integration of local language and cultural texts can strengthen students’ literacy skills, linguistic competence, and local identity awareness. Employing a qualitative approach, data were collected through classroom observations, in-depth interviews with students and lecturers, and document analysis of learning materials and student assignments. The findings reveal that the use of Maumere language elements such as traditional narratives, expressions, and cultural concepts facilitates deeper comprehension, encourages critical literacy, and enhances students’ engagement in academic discourse. The integration strategy also supports students’ ability to bridge everyday language practices with formal academic Indonesian. This study implies that culturally responsive and bilingual oriented learning can serve as an effective pedagogical strategy in higher education, particularly in multilingual contexts, while simultaneously contributing to the preservation of local languages and the development of inclusive academic literacy.